2017
DOI: 10.1103/physrevb.96.245137
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the quasiparticle peak in the spectral density of Cr(001) surfaces

Abstract: In the spectral density of Cr(001) surfaces a sharp resonance close to the Fermi level is observed in both experiment and theory. For the physical origin of this peak two mechanisms were proposed. A single particle d z 2 surface state renormalised by electron-phonon coupling and an orbital Kondo effect due to the degenerate dxz/dyz states. Despite several experimental and theoretical investigations, the origin is still under debate. In this work we address this problem by two different approaches of the dynami… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Despite its general numerical complexity, the method has been already used many times to describe the Kondo physics of atoms on a broad variety of surfaces. 273,280,281 Finally, let us conclude this section by briefly discussing a few of the outstanding problems when dealing with spin-electron interaction in a completely nonperturbative way. Firstly, it is important to point out that the electron transmission spectrum, when computed, is essentially obtained from elastic scattering to the correlated spectral function.…”
Section: Spin-electron Interactionsmentioning
confidence: 99%
“…Despite its general numerical complexity, the method has been already used many times to describe the Kondo physics of atoms on a broad variety of surfaces. 273,280,281 Finally, let us conclude this section by briefly discussing a few of the outstanding problems when dealing with spin-electron interaction in a completely nonperturbative way. Firstly, it is important to point out that the electron transmission spectrum, when computed, is essentially obtained from elastic scattering to the correlated spectral function.…”
Section: Spin-electron Interactionsmentioning
confidence: 99%
“…14 Namely a pseudogap is found below roughly 200 K and the emergence of a sharp resonance below 75 K. These observations hint in the direction of a many-body interpretation of the resonance just as recent dynamical mean-field theory (DMFT) calculations do. 15,16 For example, based on DMFT calculations within the continuous-time quantum Monte Carlo (CTQMC) solver it was observed that the resonance was very robust against artificial shifts in the one-particle energies of the d xz , d yz and d z 2 states. In contrast for DMFT calculations based on the spinpolarized T-matrix fluctuation exchange approximation, which is suitable for weakly and moderately correlated systems, no resonance was observed.…”
Section: Introductionmentioning
confidence: 99%
“…This could not be verified due to spurious behavior involved with the spin-polarized version of the NCA method. 16,17 In this work it is investigated whether the d z 2 surface state renormalized by means of the electron-phonon coupling is responsible for the experimentally observed resonance at the Fermi level of Cr(001)-surfaces. More precisely, the electron-phonon mass-enhancement factor of the Cr(001)-surface is investigated and a comparison is made with that of the bulk by means of abinitio calculations.…”
Section: Introductionmentioning
confidence: 99%